2008
DOI: 10.1016/j.devcel.2008.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Roles of Notch Signaling in the Regulation of Epidermal Development

Abstract: Recent studies have shown that Notch signaling plays an important role in epidermal development, but the underlying molecular mechanisms remain unclear. Here, by integrating loss- and gain-of-function studies of Notch receptors and Hes1, we describe molecular information about the role of Notch signaling in epidermal development. We show that Notch signaling determines spinous cell fate and induces terminal differentiation by a mechanism independent of Hes1, but Hes1 is required for maintenance of the immature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
134
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(148 citation statements)
references
References 13 publications
9
134
3
Order By: Relevance
“…Notch signaling has been shown to be important for the commitment of basal keratinocytes to terminal differentiation during development Moriyama et al, 2008;Nguyen et al, 2006;Pan et al, 2004). Although several groups have deleted Notch signaling components and analyzed keratinocyte defects, alterations in epidermal specification have not been noted to date.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notch signaling has been shown to be important for the commitment of basal keratinocytes to terminal differentiation during development Moriyama et al, 2008;Nguyen et al, 2006;Pan et al, 2004). Although several groups have deleted Notch signaling components and analyzed keratinocyte defects, alterations in epidermal specification have not been noted to date.…”
Section: Discussionmentioning
confidence: 99%
“…NICD translocates to the nucleus, where it interacts with the DNAbinding protein CSL/RBP-Jk and the coactivator Mastermind to promote the transcription of Notch target genes (Kopan and Ilagan, 2009). In the skin, canonical Notch signaling is required for the commitment of basal keratinocytes to terminal differentiation during development Moriyama et al, 2008;Nguyen et al, 2006;Pan et al, 2004). However, whether Notch signaling regulates epidermal keratinocyte specification directly is not known.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in keratinocytes, Notch1 blocks p63 expression and promotes differentiation. Conversely, p63 antagonizes Notch1 and prevents differentiation (31,34,52,53). Similarly, in mammary epithelial cells, Notch signaling reduces levels of ΔNp63 and mimics ΔNp63 depletion (35).…”
Section: Discussionmentioning
confidence: 99%
“…Monitoring the activation of the Notch pathway using an antibody against the active form of Notch, lineage-tracing experiments using Cre recombinase triggered by the activation of Notch1, or expression of Notch target gene Hes1 revealed that the Notch pathway is active mainly in suprabasal cells Vooijs et al 2007;Moriyama et al 2008). Complete inactivation of the Notch pathway in mice deficient for g-secretase 1 and 2 or multiple Notch receptors (Pan et al 2004) or the transcription factor that relays Notch signaling (RBP-Jk) or Hes1 (Moriyama et al 2008) leads to a lack of spinous differentiation and loss of skin barrier formation. Conversely, overexpression of Notch intracellular domain in the epidermis leads to spinous layer expansion (Uyttendaele et al 2004;.…”
Section: Epidermal Stratification Renewal and Differentiationmentioning
confidence: 99%